Transcriptomic analysis reveals the impact of concurrent, resistance, and endurance training on skeletal muscle - Longfei Zhao; Huangyan Li; Dongli Li; Li Luo; Shiliang Hu (PLoS ONE, 2026)
The shared and divergent molecular mechanisms underlying skeletal muscle adaptation to different exercise modalities are not fully understood. This study aimed to compare the physiological and transcriptomic responses to 12 weeks of concurrent (CET), resistance (RES), or endurance (END) training in healthy males. While all groups exhibited similar increases in lean body mass, RES and END elicited distinct functional improvements in maximal strength and aerobic capacity, respectively. Notably, CET preserved strength gains comparable to RES but showed a blunted improvement in anaerobic power. Transcriptomic analyses revealed both common and modality-specific signatures. Although the number of differentially expressed genes varied across groups (CET: 392; RES: 17; END: 49), enrichment analyses consistently identified the engagement of extracellular matrix (ECM) organization pathways. Gene set enrichment analysis further demonstrated a universal activation of ECM remodeling and an inhibition of translation initiation processes post-training. Weighted gene co-expression and protein-protein interaction network analyses pinpointed core genes associated with each modality, including COL1A1/COL1A2 for CET and END, and SPARC/ASPN for RES. Regulatory network predictions implicated the miR-29 family and JUN as potential co-regulators of collagen-related genes. In conclusion, this integrated analysis establishes ECM remodeling as a fundamental transcriptional response supporting exercise-induced hypertrophy common to diverse training modalities, while simultaneously identifying distinct gene regulatory networks that underlie their divergent functional outcomes.